Supplementation of Nucleosides During Selection can Reduce Sequence Variant Levels in CHO Cells Using GS/MSX Selection System. Issue 1 (17th August 2017) - Tang, Danming; Lam, Cynthia; Louie, Salina; Hoi, Kam Hon; Shaw, David; Yim, Mandy; Snedecor, Brad; Misaghi, Shahram
Abstract : In the process of generating stable monoclonal antibody (mAb) producing cell lines, reagents such as methotrexate (MTX) or methionine sulfoximine (MSX) are often used. However, using such selection reagent(s) increases the possibility of having higher occurrence of sequence variants in the expressed antibody molecules due to the effects of MTX or MSX on de novo nucleotide synthesis. Since MSX inhibits glutamine synthase (GS) and results in both amino acid and nucleoside starvation, it is questioned whether supplementing nucleosides into the media could lower sequence variant levels without affecting titer. The results show that the supplementation of nucleosides to the media during MSX selection decreased genomic DNA mutagenesis rates in the selected cells, probably by reducing nucleotide mis‐incorporation into the DNA. Furthermore, addition of nucleosides enhance clone recovery post selection and does not affect antibody expression. It is further observed that nucleoside supplements lowered DNA mutagenesis rates only at the initial stage of the clone selection and do not have any effect on DNA mutagenesis rates after stable cell lines are established. Therefore, the data suggests that addition of nucleosides during early stages of MSX selection can lower sequence variant levels without affecting titer or clone stability in antibody expression. Abstract : In the process of generating stable monoclonal antibody (mAb) producing cell lines, using MSX as the selective agent to inhibit glutamine synthase (GS) causes both glutamine and nucleotides starvation. Nucleotides starvation can increase the possibility of having sequence variants in the expressed antibody molecules. In this study, it is shown that supplementation of nucleosides in the media during MSX selection reduces DNA mutagenesis, possibly by preventing the mis‐incorporation of defective nucleotides into the DNA. Furthermore, the data suggest that nucleosides supplementation during MSX selection does not affect selection stringency but increases clone recovery rate, making it suitable for generation of stable mAb expressing cell lines.